2004
DOI: 10.1002/app.13691
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic, structural, and thermal degradation of a tercopolymer derived from salicylic acid, guanidine, and formaldehyde

Abstract: ABSTRACT:A salicylic acid-guanadine-formaldehyde (SGF) tercopolymer was synthesized by the condensation of salicylic acid with guanidine carbonate and formaldehyde in 1 : 1 : 2 molar proportions in the presence of 2M HCl as a catalyst. The SGF tercopolymer was characterized on the basis of elemental analysis and ultraviolet-visible, IR, and NMR spectral studies. The Freeman-Carroll and SharpWentworth methods were used to calculate the activation energy and thermal stability of the tercopolymer. Kinetic paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…It is observed that the molecular weight of terpolymer increases with the increase in hexamethylenediamine content. This observation is in agreement with the trend observed by earlier researchers [17]. Conductometric titration curve of terpolymer was shown in Figure 2 and the results are presented in Table 2.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It is observed that the molecular weight of terpolymer increases with the increase in hexamethylenediamine content. This observation is in agreement with the trend observed by earlier researchers [17]. Conductometric titration curve of terpolymer was shown in Figure 2 and the results are presented in Table 2.…”
Section: Resultssupporting
confidence: 92%
“…The thermal stability of terpolymers has been extensively studied by employing the method of thermogravimetric analysis (TGA) by several authors [12][13][14][15][16][17][18][19][20][21]. Thermoanalytical and kinetic studies of terpolymer resins derived from 8-hydroxyquinoline-5-sulphonic acid/p-cresol, oxamide/melamine with formaldehyde have been reported by Singru et al [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Thermogram of all 2, 2'-HBBF copolymer exhibited two stages of decomposition after loss of water molecules. It is observed from TG data of these copolymer resins that the sample lost 3.81 to 6.58% of its weight when the temperature was raised to 180 0 C. This initial weight loss may be attributed to solvent or moisture entrapped in the copolymer samples [21][22][23][24] . First decomposition step in 2, 2'-HBBF copolymer resin represents % Mass loss degradation of both phenolic hydroxyl groups.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…Patel and Lad12 reported the novel terpolymers: poly(keto‐amine‐ureas) and studied the glass reinforcement of such terpolymer‐ epoxy systems. Michael and coworkers have reported the synthesis, structural, and thermal degradation of a polymer derived from salicylic acid, guanidine, and formaldehyde 13. Synthesis, characterization, and ion exchange properties of 4‐hydroxyacetophenone, biuret, and formaldehyde terpolymer resin were studied by Gurnule et al14 Ion exchange resin derived from semicarbazone and oximes of 2‐hydroxy acetophenone‐substituted benzoic acid‐formaldehyde studied by Nayak and coworkers 15, 2.…”
Section: Introductionmentioning
confidence: 99%